MAKANAN KODOK Bufo melanostictus PADA BEBERAPA HABITAT DI SAWAHLUNTO - Wulan, Darma - (STKIP PGRI Sumbar, 2014)
Sawahlunto community social activities that have always depended on nature suchas forest management for agriculture and the rapid rate of population growthresulting in the rapid expansion of settlements, leading to loss of habitat andwetlands. The decrease in natural population of Bufo melanostictus resulting balanceof the food chain in the ecosystem becomes disrupted. The study was conducted inJune 2014. Sampling was done by direct survey of the species Bufo melanostictusobtained at the scene, the observer walks along the specified location. If you lookdirectly capture and grab samples. Identification of food frog conducted at theLaboratory of Zoology Biology Education Program STKIP PGRI West Sumatra.The results showed that food frog frogs are generally found in the stomach is aninsect, the type of location I 6, 6 and 5 Family Order, in Area II, as many as 13species, 9 and 8 Family Order, in Area III found as many as 15 species, 8 Familyand 7 of the Order, while the fourth location is found 7 species, 5 and 5 FamilyOrder.